Estudos bioeletroquímicos de nitroquinonas derivadas da Nor-β-Lapachona - Souza, Antonio Albuquerque de (2011)
Quinones have been the subject of much interest due to their various biological activities, mainly as antitumor and as trypanocidal agents. Quinones are cytotoxic by two main mechanisms: the generation of ROS resulting in oxidative stress and alkylation of cellular nucleophiles, such as DNA and some enzymes such as topoisomerases. Their activity depends on bioreduction, similarly to what happens to nitroaromatic compounds. They also catalyze electron transfer reactions in biological processes and, after reduction generate radical anions (semiquinone radical anion and nitro), which depending on stability, can furnish their free electrons to acceptor molecules. In the present study, compounds with mixed functionalities derived from nor-β-lapachone, including a nitroaniline group were electrochemically studied in protic (acetate buffer) and aprotic (DMF+TBABF4, DMSO+TBAP and Acetonitrile+TBABF4) media, using glassy carbon and mercury as working electrodes. The compounds showed a complex redox behavior and the mechanism was elucidated using electron spin resonance. The electroreduced products of nor-β-lapachone and of the nitroquinones reacted with oxygen, indicative of the generation of reactive oxygen species, reactivity in the order of 2 > nor-β-lapachone > 3 > 1. We investigated their interaction with DNA, which was shown to be positive for nitroquinones and negative for the precursor nor-β-lapachone, in agreement with biological assays which had also shown that the nitroquinones cause DNA damage. The stability of the nitrosemiquinones, their half-life times were measured using mercury electrode, and the reaction rates for the electrochemical process-following-up-isproportionation reaction were measured. From these studies, a lower stability for the meta-substituted nitrophenylaniline (k2 = 5.188 x 103 L mol-1 s-1 and t1/2 = 0.06 s) was evidenced. Upon spectroelectrochemical reduction studies of the nitroquinones, the generation of radicalar intermediates (semiquinone radical anion and nitro radical anion) was observed, with differences between o- and m-derived compounds and the p-substituted one. To increase the solubility of the nitroquinones, in order to allow in vivo studies, the formation of inclusion complexes with β-cyclodextrin were evaluated. Positive results were obtained, leading to a viable formulation alternative for further biological studies with the compounds.